PENGARUH PENGGUNAAN CHATGPT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 9B PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 7 BUTON - Ningsi, Salsya; Madi; La Jusu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify whether the use of Chatgpt can increase students’ learning motivation and how it influences students’ understanding of the taught material. This research is an experimental study conducted by applying Chatgpt to improve students’ learning motivation. The population and sample of this study consisted of one class with a total of 24 students’. The sampling technique used was total sampling. The date collection techniques in this study were a learning motivation questionnaire consisting of 15 essay questions. The instruments werw first tested for validity, and item difficulty level. The date analysis techniques used were descriptive statistics, prerequisite analysis tests, and hypothesis testing. The results of the hypothesis testing showed that: (1) there was a positive and significant effect of Chatgpt usage in increasing students’ learning motivation, with a significance value (5.432>1.717) and (2) there was a positive and significance value of (0.000<0.05) and significancteffect of Chatgpt usage in increasing students’ learning motivation, with a significance value of (0.000 < 0.05) and a t-count greater than the t-table value (4.256>1.717). Thus, it can be concluded that the use of Chatgpt has a positive and significant effect on increasing the learning motivation of class IX B students’ in the Islamic religious education subject at SMP Negeri 7 Buton